Medical Practice in the Peripheral Health Centers in Nepal - Sitaula, S; Magar, A (Journal of Nepal Health Research Council, 2011)
The Ministry of Health and Population has implemented a compulsory two year service contract in government health facilities for all the scholarship holders of the Ministry of Education. Doctors are now being deployed to all hospitals and primary health centers of the country. Prior to 2005 it was very difficult to send doctors to the peripheral part, and now they wish to go more remote area due to the privilege given to the National Academy of Medical Sciences Post Graduate Entrance Examination, which help them get MD/MS seat. However, there are more challenges due to weak health system and failure to implement established rule and regulation. This paper highlights the outcry of a doctor working in the remote part of the country.